The unit of the right of private insurances: the application of the legislation of insurances (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Private insurance regulation has increasingly gathered importance since it noonly affects the insurance industry, but also the economy as a whole, as a tool toassure provisions and savings.The protracted regulation on the matter, both at a national and European level, requires an extra effort to liaise those public and private law norms that regulate different forms of insurance contracts. Therefore, the aim of this article is to serve as apractical guide to those who need to analyse the insurance institution.
Keywords: public supervision; private insurance framework; interdisciplinary regulation; regulatory approaches; consumer protection